HARMONIZATION OF ISLAM AND LOCAL TRADITION (Ethnographic Studies in the Construction of Food Culture of the Bawean Telukjatidawang Community) - Nur Syarifuddin; Yaqub Cikusin (Universitas Islam Malang, 2022)
Culture is something that will affect the level of knowledge and includes a system of ideas or ideas contained in the human mind in everyday life, There are two things that affect humans in obtaining their culture, namely related to the biological adaptation environment and cultural adaptation. There is an interesting thing when culture is juxtaposed with religion. Culture itself has three values, namely the value of religion, art and solidarity related to taste and hinges on feelings, intuition, and imagination. Expressive culture is generally conservative in character (Sjahbana, 2003: 3).In this context, the food culture of the Bawean community of Telukjatidawang Village can be seen as a religious expression that can be observed sociologically and is the result of community construction. As a belief system, religion is manifested in social systems and behavior by its adherents in public life. Religion is related to human experience both as individuals and groups, so that every behavior he plays is always related to the belief system of the religious teachings he adheres to. Individual and social behavior is driven by internal forces based on the values of religious teachings that were previously internalized in the Bawean community of Telukjatidawang Village. Religion is something that is final, universal, eternal (parennial) and knows no change (absolute). While culture is particular, relative and temporary. Religion without culture can indeed develop as a personal religion, but without culture, religion as a collectivity will have no place (Darori, 2000: 11). Islam responds to local culture, there are traditions wherever and whenever, and is open to accepting local culture, customs or traditions as long as they do not conflict with the spirit of the Qur'an and Sunnah. Likewise with Islam that developed in Bawean society which is very thick with tradition and culture.Ã‚Â Keywords:Ã‚Â Harmonization, Islam, Local Traditions